Mature cystic teratoma tumor markers in LARA - Kavak, Salih Burçin; Çelik, Ebru; Gürateş, Bilgin; Baykuş, Yakup; Çelik, Hüsnü (Gunes Kitap Kirtasiye, 2013)
Purpose: The aim of this study is to overview our experience in surgical treatment of mature cystic teratomas (dermoid cysts) and to examine the relation with tumor markers. Material and Method: We retrospectively analysed the results of 122 patients who underwent laparoscopy or laparotomy due to dermoid cysts and in whom dermoid cysts were diagnosed during cesarean section incidentally between the years 2005 and 2011 in our clinic. From the records; the age of the patients, preoperative size of the cysts, bilaterally or unilaterally, tumour markers, operation type and pathologic results are abtained. Descriptive statistics were used to assess the data and variables used in% and the mean ± standard deviation. Findings: Surgically treated dermoid cysts were between 3-25 cm and mean size was 7.38±3.69 cm. In 92 patients, laparoscopy performed and in 30 patients laparotomy was the method of operation. Among patients underwent laparotomy; 10 patients were in postmenopausal period and had additional problems since myoma uteri or different cervical neoplastic lesions. 6 patients underwent laparatomy because of the large tumour size (>15 cm). In 14 patients dermoid cysts were observed incidentally during cesarean sections and were extirpated. CA 125 levels are found high in statisticially significant levels in bilateral tumours. It is also found that CA 19-9 levels increase to statisticially significant levels in tumours bigger than 15 cm in diameter. Conclusion: Mature cystic teratomas can reach to very big sizes and treatment can be done surgically. It must be remembered in mind that in cases with high CA 125 levels, the dermoid cyst may be bilateral and CA 19-9 levels may be high in dermoid cysts bigger than 15 cm.
Matür kistik teratomlarda tümör markerleri
Keywords: Ca 125; Ca 19-9; Mature cystic teratoma; Surgical treatment